DESIGN OF A PROTOTYPE MONITORING SYSTEM FOR SCHOOL LIBRARY VISITORS USING RFID AND NODEMCU BASED ON THE INTERNET OF THINGS - Sofyan; Muh Imam Quraisy; Mardewi; Siti Nur Asia (Bajang Institute, 2021)
Monitoring the identity of library visitors is a very important part. Usually to monitor students who are diligent in visiting the school library by providing books or guest books, the purpose of this study is to record the identity of students who visit the library electronically, in the study describes the monitoring system for library visitors with internet communication lines, database storage media by using descriptive method. The design of this system consists of a library card, RFID, Nodemcu, 2 x 16 LCD, and a web as an application used to process visitor identities or as a place to display information in real time. The web application design uses the programming language HyperText Markup Language (HTML), Cascading Style Forms (CSS), Hypertext Preprocessor (PHP), Content Management System (CMS) using a MySQL database while the test results show that this system can work well, with the The school library visitor monitoring system using internet-based RFID and nodemcu can make it easier for employees to view and process the identity of library visitors